Strengthening the Criminal Law System for National Defense Against Automated Cyber Attacks Based on “Artificial Intelligence” - Adriani Maylinda Christina Linda (West Science Law and Human Rights, 2026)
The development of artificial intelligence (AI) has given rise to automated cyberattacks such as botnets, deepfakes, and adaptive DDoS attacks that challenge the Indonesian criminal justice system due to the complexity of perpetrator identification, legal evidence, digital anonymity, and regulatory gaps in the ITE Law No. 11/2008 and the PDP Law No. 27/2022. This multidisciplinary legal normative research analyzes these challenges through expert interviews, TensorFlow simulations, and a comparison of Indonesia, Japan, and the Netherlands, resulting in the innovative concept of the "Penal AI Attribution Spectrum" for AI-based autonomous criminal attribution and the "AI Penal Readiness Index" (Indonesia's score is 45/100). Current regulations are considered not yet adaptive to the autonomous and global modus operandi of AI, with prospects for strengthening through the 2025 Cyber Security and Resilience Bill (KKS), AI forensic training, and collaboration between the National Cyber Security Agency (BSSN), the Indonesian National Police (Polri), and the Ministry of Law and Human Rights (Kemenkumham) similar to Europol EC3. The conclusion recommends reform of the ITE/PDP Law with an "AI-Enabled Cybercrime" chapter, a cross-sectoral task force, and harmonization of the ASEAN-Budapest Convention for a robust, ethical, and just criminal law system in the digital era.